Development of a flow cytometric panel to assess prognostic biomarkers in fine needle aspirates of canine cutaneous or subcutaneous mast cell tumors - Wu, BinXi; Lejeune, Amandine; Affolter, Verena K.; Iamone, Giulia; Riondato, Fulvio; Kol, Amir (Frontiers in Veterinary Science, 2023)
Mast cell tumor (MCT) is a common skin cancer in dogs that has a wide range of clinical behaviors.The purpose of this study was to develop a novel multicolor flow cytometry (FC) panel that will enable the quantification of candidate prognostic markers (Ki-67 and pKIT) in fine needle aspirate (FNA) samples prior to surgical removal of the tumors. FNA of canine MCTs and the NI-1 cell line were utilized to develop a FC panel that includes a viability dye (FVS620, BD Biosciences; 7-AAD, Invitrogen) and the following primary conjugated antibodies: CD117-PE (ACK45, BD Biosciences), pKIT-A647 (polyclonal bs-3242R, BIOSS) and Ki-67-FITC (20Raj1, eBioscience; MIB-1, DAKO). A total of nine FNA samples of canine MCTs were collected, seven out which produced sufficient cells for FC analysis. The Ki-67 antibody clone 20Raj1 produced a positive signal when applied to blood leukocytes but failed to provide robust labeling of neoplastic mast cells. The Ki-67 antibody clone MIB-1 delivered a superior staining quality in both the NI-1 cells and primary MCT cells. CD117-PE signal was adequate post fixation and permeabilization and in the combination of 7-AAD. pKIT produced non-specific staining and was not suitable for this multicolor FC panel. In conclusion, FNA samples of canine MCTs can often yield adequate cell numbers for FC analysis, and a multicolor FC panel was developed that can detect Ki-67 in canine mast cells. This would permit further studies into the potential use of this panel for canine cutaneous and subcutaneous MCT prognostication purposes.